A pivotal role for tryptophan 447 in enzymatic coupling of human endothelial nitric oxide synthase (eNOS): effects on tetrahydrobiopterin-dependent catalysis and eNOS dimerization. - Benson, M; Batchelor, H; Chuaiphichai, S; Bailey, J; Zhu, H; Stuehr, D; Bhattacharya, S; Channon, K; Crabtree, M (2013)
Tetrahydrobiopterin (BH4) is a required cofactor for the synthesis of NO by NOS. Bioavailability of BH4 is a critical factor in regulating the balance between NO and superoxide production by endothelial NOS (eNOS coupling). Crystal structures of the mouse inducible NOS oxygenase domain reveal a homologous BH4-binding site located in the dimer interface and a conserved tryptophan residue that engages in hydrogen bonding or aromatic stacking interactions with the BH4 ring. The role of this residue in eNOS coupling remains unexplored. We overexpressed human eNOS W447A and W447F mutants in novel cell lines with tetracycline-regulated expression of human GTP cyclohydrolase I, the rate-limiting enzyme in BH4 synthesis, to determine the importance of BH4 and Trp-447 in eNOS uncoupling. NO production was abolished in eNOS-W447A cells and diminished in cells expressing W447F, despite high BH4 levels. eNOS-derived superoxide production was significantly elevated in W447A and W447F versus wild-type eNOS, and this was sufficient to oxidize BH4 to 7,8-dihydrobiopterin. In uncoupled, BH4-deficient cells, the deleterious effects of W447A mutation were greatly exacerbated, resulting in further attenuation of NO and greatly increased superoxide production. eNOS dimerization was attenuated in W447A eNOS cells and further reduced in BH4-deficient cells, as demonstrated using a novel split Renilla luciferase biosensor. Reduction of cellular BH4 levels resulted in a switch from an eNOS dimer to an eNOS monomer. These data reveal a key role for Trp-447 in determining NO versus superoxide production by eNOS, by effects on BH4-dependent catalysis, and by modulating eNOS dimer formation.